Andrological diagnostics - Köhn, F-M; Haidl, G (Urologe. Ausgabe A, 2007)
Andrology was included as a further subject for continuing education in the Model Ordinance on Continuing Education at the 106th German Physicians Meeting in Cologne in 2003. In addition to fertility disorders, this discipline comprises medical care for men with fertility disorders, erectile dysfunction, disorders of libido, ejaculation and coitus, various forms of hypogonadism, and delayed puberty. Furthermore, this field also covers questions concerning male contraception, gynecomastia, and male senescence. Diagnostic procedures in andrology require close interdisciplinary cooperation between gynecologists, human geneticists, and specialists in psychosomatic medicine. They include medical history, clinical examination, and laboratory analyses. Except for confirming azoospermia, it is not possible to make a definitive prognosis of fertility based on semen analysis. Functional tests allow a better assessment of the spermatozoa's fertility since 25-30% of men desiring a child exhibit reduced spermatozoan functions which cannot be verified on routine semen analysis.